Distinguishing atypical chronic myeloid leukemia from other Philadelphia-negative chronic myeloproliferative neoplasms. Issue 2 (March 2020) - Sadigh, Sam; Hasserjian, Robert P.; Hobbs, Gabriela
Abstract : Purpose of review: Atypical chronic myeloid leukemia (aCML), BCR-ABL1 -negative, is a rare myelodysplastic/myeloproliferative neoplasm (MDS/MPN) characterized by leukocytosis, granulocytic dysplasia, and typically poor patient outcomes. Since its first description as a variant CML lacking the Philadelphia chromosome (Ph), the diagnostic criteria for aCML have evolved significantly. Nevertheless, distinguishing it from other Ph-negative myeloid neoplasms can still be very challenging, and given its generally worse prognosis, this is a clinically important distinction. The purpose of this review is to conceptualize our understanding of aCML molecular genetics based on recent advances, and describe how genetic features can be used in conjunction with clinical and morphologic features to better diagnose this elusive entity. Recent findings: The classification criteria for aCML have evolved and changed multiple times over the past decades, and is now based on strict application of morphologic, clinical and laboratory criteria. Recent work has elucidated the mutational landscape of aCML, especially with respect to potentially differentiating profiles compared with other Ph-negative myeloid neoplasms. Summary: Atypical CML is a rare MDS/MPN overlap syndrome that can be diagnostically challenging; however, its emerging molecular genetic understanding and clinicomorphologic phenotype can help in distinguishing it from other Ph-negative myeloid neoplasms.